Late holocene climate changes in the altai region based on a first high‐resolution biomarker isotope record from lake khar nuur - Bliedtner, Marcel; Struck, Julian; Strobel, Paul; Salazar, Gary; Szidat, Sönke; Bazarradnaa, Enkhtuya; Lloren, Ronald; Dubois, Nathalie; Zech, Roland (Geophysical Research Letters, 2021)
The Late Holocene marks a substantial cultural and economic transition in the eastern Eurasian Steppe and Altai Region with the dispersal of nomadic pastoralism. So far, paleoclimate conditions during this time remain unclear and controversial. Here, we present a high‐resolution 4.2 ka paleoclimate record from Lake Khar Nuur in the Mongolian Altai that is based on lake sediment proxies and biomarker compound‐specific δ 2 H analyses. Our results document increased aridity before ∼3.7 cal. ka BP, followed by two pronounced phases of warm and wet conditions from ∼3.5–2.8 to ∼2.3–1.5 cal. ka BP, and a strong increase in aridity since ∼1.5 cal. ka BP. Phases of warmer and wetter conditions coincide with a negative North Atlantic Oscillation, which has been responsible for advecting moisture into the region by more southerly‐displaced Westerlies and possibly favored the expansion of mobile nomadic pastoralism in the region.